PENINGKATAN HASIL BELAJAR PENJUMLAHAN DAN PENGURANGAN MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS 2 SDN 69 GALESONG 1 - Indah Trinawati; Sri Rahayu Anugrah; Nural Miftahul Jannah; Harisatul Jannah; Sri Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the mathematics learning outcomes of second-grade students at SDN 69 Galesong 1 on the material of addition and subtraction of integers through the use of pictorial media. The research employed the Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action, observation, and reflection phases. The research subjects were 35 students. Data were collected through observation, tests (pre-test and post-test), and documentation. The results showed a significant improvement in student learning outcomes. The average pre-test score was 59.2 with a mastery rate of 31.4%, which increased to 72.4 with a 65.7% mastery rate in Cycle I, and reached 84.6 with a 91.4% mastery rate in Cycle II. Furthermore, teacher and student activities during the learning process showed significant improvement, reflecting increased student motivation and engagement. These findings indicate that the use of pictorial media is effective in helping students understand integer operation concepts more concretely, attractively, and easily. Thus, pictorial media can serve as an innovative alternative learning strategy to enhance mathematics learning outcomes in elementary schools.